Konsep Jual Beli dalam Perspektif Fiqih Muamalah dan Implikasinya Terhadap Ekonomi Syariah - Nabila Azrilia Syahra; Fitriana Yasintha; Rawdia Tuzahara; Nur Azmi; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the concept of buying and selling from the perspective of muamalah fiqh and its implications for sharia economics. Buying and selling, as one of the most common economic transactions, has a strong legal basis in muamalah fiqh which regulates the principles of justice, transparency and certainty in trade. This research identifies various forms of transactions that are permitted and prohibited in sharia, as well as legal conditions for buying and selling. Through a normative analysis approach and case studies, this article also explores the impact of applying the principles of muamalah fiqh on sharia economic growth, including how sharia-compliant transactions can increase public confidence in business, encourage the growth of small businesses, and create more equitable prosperity.